2006
DOI: 10.1016/j.ejcts.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical versus bioprosthetic valve replacement in middle-aged patients

Abstract: In middle-aged patients, MAPE may occur more often in patients with bioprosthetic valves, but definitive conclusions necessitate the accumulation of additional follow-up. At present, these data do not support lowering the usual cutoff for implantation of a tissue valve below the age of 65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 13 publications
6
85
2
1
Order By: Relevance
“…Also, Kulik et al [27] found a survival curve similar to the present study when evaluating a cohort of 423 patients, aged between 50 and 70 years who underwent aortic valve replacement between January 1977 and July 2002, with a mean of 4.9 ± 3.9 years and a maximum of 15.8 years. The survival at 5, 10 and 15 years after surgical valve replacement by a mechanical substitute was 89.0 ± 2.1%, 73.2% ± 4.2 and 65.3 ± 6.0% and by biological substitute was 87.6 ± 5.7%, 75.1 ± 12.6% and 37.5 ± 27.3%, respectively, with no statistically significant difference between groups (P=0.55).…”
Section: Fig 3 -Kaplan-meier Time To Assess Event-free Bleedingmentioning
confidence: 57%
See 1 more Smart Citation
“…Also, Kulik et al [27] found a survival curve similar to the present study when evaluating a cohort of 423 patients, aged between 50 and 70 years who underwent aortic valve replacement between January 1977 and July 2002, with a mean of 4.9 ± 3.9 years and a maximum of 15.8 years. The survival at 5, 10 and 15 years after surgical valve replacement by a mechanical substitute was 89.0 ± 2.1%, 73.2% ± 4.2 and 65.3 ± 6.0% and by biological substitute was 87.6 ± 5.7%, 75.1 ± 12.6% and 37.5 ± 27.3%, respectively, with no statistically significant difference between groups (P=0.55).…”
Section: Fig 3 -Kaplan-meier Time To Assess Event-free Bleedingmentioning
confidence: 57%
“…The cohort studied by Kulik et al [27] showed no differences from bleeding events among patients with biological and mechanical substitutes (P=0.74), as well as the trial by Stassano et al [24] (P = 0.08). This last attributed this result to the possibility of low-intensity anticoagulation for patients with mechanical prostheses in the sample and/ or the possibility of patients with biological prostheses have received anticoagulation during follow-up.…”
Section: Bleeding Eventsmentioning
confidence: 98%
“…14) On the other hand, there have been some reports that did not support lowering the cutoff age for B valves to less than 65 years because of insufficient evidence. [15][16][17] Forcillo et al found that the rate of freedom from reoperation for SVD of the CarpentierEdwards pericardial valve averaged 60% and 30% at 15 and 20 years after surgery, respectively, in patients younger than 60 years of age compared with 90% at 15 years after surgery in patients 60 to 70 years of age and 99% at 10 years after surgery in patients older than 70 years of age. 18) Aupart et al reported that actuarial freedom from SVD at 18 years varied from 99% in patients aged 70 years to 77% in those aged 60 to 70 years, and 45% in patients younger than 60 years and patient age was the only factor to influence durability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ruel et al 10 also considered that the higher rate of embolic events might be confounded with the higher co-prevalence of atrial fibrillation in mitral valve diseases, which we agree with. Interestingly, the study by Kulik et al 11 , comparing mechanical versus bioprosthetic valve replacement in middle-aged patients, suggests that these patients are not free from major adverse prosthesis-related events. In addition, according to Khan et al 12 , the primary difference observed in outcomes between mechanical and tissue bioprostheses was a higher risk of hemorrhage in the aortic mechanical valve recipients and a higher risk of structural failure in all tissue valve recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of tissue valve reoperation would outweigh the constant risk of anticoagulant-related hemorrhage with mechanical valves 12 . Therefore, Kulik et al 11 suggest that the use of a mechanical prosthesis may be at least as good as, and possibly better than the use of bioprostheses in middle-aged patients. We do not think, based on all socioeconomic issues in developing countries that the mechanical prosthesis is better than the bioprosthesis, but we do believe that it may be at least as good as the bioprosthesis.…”
Section: Discussionmentioning
confidence: 99%